Functional genomics for parasitic nematodes and platyhelminths. - Aboobaker, A; Blaxter, M (2004)
Understanding the molecular basis of parasitism, particularly that linked to human disease, is one of the most important frontiers in biology. A major impediment to the direct analysis of the genes of nematode and platyhelminth parasites is the practical impossibility of investigating their function with any of the genetic methods used so effectively for many multicellular model organisms and unicellular parasites. Emerging 'post-genomic' techniques have been developed to study gene function both directly and indirectly in nematode and flatworm parasites, and can use the information from the parasite genome projects. Among these, the reverse genetic technique of RNA interference could be most effective in determining the function of genes essential to parasite survival and hence uncovering novel therapeutic targets.